Visitors’ Willingness to Pay for Mangrove Conservation: Case Bale Mangrove Ecotourism - Muhammad Rizqy Al Furqon; Muhamad Bai’ul Hak (Program Studi Ekonomi Pembangunan Fakultas Ekononomi Universitas Simalungun, 2025)
This research aims analyze the visitors’ willingness to spend their budget for mangrove conservation. The research type is a quantitative approach. The data collection technique used is an in-depth and face-to-face interview. Population in this research is all visitors of Bale Mangrove Ecotourism. By using accidental sampling, a questionnaire was used as a data collection tool with a total of 99 respondents. The study applied the Travel Cost Method (TCM) to measure the willingness to pay for visitors to preserve the mangrove. The result shows that, the visitors are Willing To Pay (WTP) is IDR.11,209,680 (711,74 USD) per 1,000 visit and the average willingness to pay is IDR.8,595 (0,55 USD) per one visit. Based on the results of statistical analysis, total cost of travelling and environmental awareness impact positive significantly to willingness to pay. The other factors, are income, level of education, dependant, and age affect positive insignificantly to Willingness to pay. On the other hand, the distance factor influence negative insignificantly on WTP